The antidepressant standoff: why it continues and how to resolve it. Issue 2 (29th January 2020) - Ormel, Johan; Spinhoven, Philip; de Vries, Ymkje Anna; Cramer, Angélique O. J.; Siegle, Greg J.; Bockting, Claudi L. H.; Hollon, Steven D.
Abstract: Background: Antidepressant medications (ADMs) are widely used and long-term use is increasing. Given this extensive use and recommendation of ADMs in guidelines, one would expect ADMs to be universally considered effective. Surprisingly, that is not the case; fierce debate on their benefits and harms continues. This editorial seeks to understand why the controversy continues and how consensus can be achieved. Methods: 'Position' paper. Critical analysis and synthesis of relevant literature. Results: Advocates point at ADMs impressive effect size (number needed to treat, NNT = 6–8) in acute phase treatment and continuation/maintenance ADM treatment prevention relapse/recurrence in acute phase ADM responders (NNT = 3–4). Critics point at the limited clinically significant surplus value of ADMs relative to placebo and argue that effectiveness is overstated. We identified multiple factors that fuel the controversy: certainty of evidence is low to moderate; modest efficacy on top of strong placebo effects allows critics to focus on small net efficacy and advocates on large gross efficacy; ADM withdrawal symptoms masquerade as relapse/recurrence; lack of association between ADM treatment and long-term outcome in observational databases. Similar problems affect psychological treatments as well, but less so. We recommend four approaches to resolve the controversy: (1) placebo-controlled trials with relevant long-term outcome assessments, (2) inventive analyses of observational databases, (3) patient cohort studies including effect moderators to improve personalized treatment, and (4) psychological treatments as universal first-line treatment step. Conclusions: Given the public health significance of depression and increased long-term ADM usage, new approaches are needed to resolve the controversy.